Współczesne zasady chronobiologii stosowane we wczesnośredniowiecznych wspólnotach monastycznych na podstawie reguł Augustyna z Hippony, Cezarego z Arles i Benedykta z Nursji - Cyrek, Olga (Poznańskie Studia Teologiczne, 2012)
The article describes the daily schedule of monks who live according to the rules of Augustine of Hippo, Caesarius of Arles and Benedict of Nursia based on the principles of chronobiology. The authors of the monastic rules took into account not only the external conditions, the prevailing climate, but also the natural predisposition of the human body. Monks have to adapt to changes during the year, because they know that the length of night and day changes in each season of the year. Monks carry out their work and adapt well to time-related circadian succession of the cycles of light and darkness. They devote the remaining hours to physical work and other activities of a spiritual or intellectual character. Usually, they arraged their daily schedule in such a way that they could easily perform all their duties. The founders of the rules took into account the body’s natural needs and showed considerable psychological knowledge because they wanted the monks to do nothing contrary to nature and to the maintenance of their health. Although they set the appropriate hours of performing physical labor, engaging in intellectual pursuits, or prayer, they did not always stick to these rules and if necessary, used dispensation. Keywords